Effects of short-form video application users’ guanxi on intention to visit rural tourism destinations: The moderating role of tourism fatigue - Liao, Shan-Shan; Lin, Ching-Yuan; Xie, Xing-Zheng (Journal of vacation marketing, 2024)
Short-form video applications (SFV apps) provide an ideal channel for promoting rural tourism. Based on the elaboration likelihood model, this study integrated guanxi, telepresence, destination image, and tourism fatigue to investigate the factors affecting user intentions to travel to rural tourism destinations in the context of SFV apps. Through the use of structural equation modeling (SEM) and fuzzy-set qualitative comparative analysis (fsQCA), the theoretical framework was examined using data collected from 445 SFV app users. The SEM findings revealed that guanxi could directly affect argument quality and source credibility, which further strengthened destination image and telepresence; the travel intention could be affected by destination image and telepresence without guanxi. Also, tourism fatigue played three roles in the formation of travel intention. Additionally, the results of fsQCA illustrated three configurations leading to high and low intention to visit rural tourism destinations.